Comparison of KOH with Culture in the Diagnosis of Dematophytic Fungal Infection in a Tertiary Care Hospital - Kataria, Shaveta; Galhotra, Shipra; Kapoor, Priya; Jindal, Neerja; Bains, Trimaan Kaur; Kansal, Rinkal Kaur (Annals of Pathology and Laboratory Medicine, 2021)
Background: Skin mycoses also called dermatophytosis is the most common fungal infection affects 20-25% of World population. Its prevalence varies place to place with climatic changes, time to time with age, sex and lifestyle of the population. Dermatophytoses could be caused by dermatophytes and non-dermatophytes, their frequency of isolation differs with geographical variation. Objectives: To study various clinical presentations of skin mycosis and compare KOH with culture in the diagnosis of dermatophytic infections in a tertiary care hospital. Material & Methods: A total of 98 skin scrapings collected from consecutive OPD patients from 1st June 2016 to 31st May 2017 examined using KOH and culture on modified Sabouraud’s dextrose agar medium. The isolated fungi were identified by morphology, lactophenol cotton blue, slide culture and biochemical tests. Results & Discussions: T. corporis (40.82%) was the most common clinical presentation followed by T. cruris (17.35%), T. pedis (15.31%), T. capitis (8.16%). Fungal infections were demonstrated in 52/98(53.06%). The male to female ratio of the positive cases was 15:9. The most affected age group in males 30-40yrs and females 40-50yrs. KOH positive were 43.87% (43/98). The samples which were positive in both KOH and culture were 17.35% (17/98), those positive in KOH and culture negative were 26.53% (26/98) and KOH negative and culture positive were 7.14% (7/98). Out of 24 positive cultures, 21 were dermatophytes and three were non-dermatophytes. The most common dermatophytes were T. mentagrophytes (62.5%) followed by T. rubrum (20.8%) and M. gypseum (4.33%). Conclusion: Skin mycoses is caused mainly by dermatophytes (T. mentagrophytes followed by T. rubrum) but non-dermatophytic infections do occur. Therefore, fungal culture is imperative for correct diagnosis and proper treatment.